RAFFLESIA AND ITS HABITAT CHARACTERISTICS IN MANDAPAJAYA FOREST, KUNINGAN DISTRICT, WEST JAVA PROVINCE, INDONESIA - Toto Supartono; Nina Herlina (Journal of Forestry And Environment, 2018)
Rafflesia is a rare species and its distribution has never been recorded in forest areas of Kuningan District. The study aimed to describe the morphology and identify Rafflesia species, analyze the physical environment, host species characteristics, and vegetation. The methods used were a direct measurement of morphology, physical environmental conditions and host plant characteristics, and sample plots of vegetation characteristics. The results showed that the Rafflesia species found in Kuningan District was Rafflesia rochussenii and occupied a very steep and rocky location.  The host species was liana and possibly belong to the genus Tetrastigma and the trees vegetation were dominated by Villebrunea rubescens species. Keywords : conservation, endemic, Rafflesia rochussenii, rare species, Tetrastigma